Blood Profile and Carcass Production of Broiler Chickens Given Nucleotides and Turmeric Extract in Feed - Amani Aldiyanti; Elly Tugiyanti; Bambang Hartoyo (Buletin Peternakan, 2022)
Broiler chickens are birds that grow very fast, but have low body resistance and are easily stressed. This study aimed to examine the effect of nucleotide and turmeric extract (Curcuma longa Linn) on blood profile (erythrocytes, hemoglobin and leukocytes) and carcass production (weight of carcass, weight of breast, thighs and wings) in broiler chickens. Data was collected using a completely randomized design with 7 treatments consisting of Control: basal feed + antibiotic Bacitracin Zinc 0.1 g/day; N 0 : basal feed; N 1 : basal feed + turmeric extract 600 mg/kg feed; N 2 : basal feed + nucleotide 250 mg/kg feed; N 3 : basal feed + nucleotide 250 mg/kg feed + turmeric extract 600 mg/kg feed; N 4 : basal feed + nucleotide 500 mg/kg feed; N 5 : basal feed + nucleotide 500 mg/kg feed + turmeric extract 600 mg/kg feed. The results showed that nucleotide supplementation and turmeric extract had no significant effect on weight of carcass, weight of breast, thighs and wings, hemoglobin, erythrocytes and leukocytes of broiler. The use of nucleotide and turmeric extract could not improve the blood profile of broiler.